The pathology of chronic obstructive pulmonary disease - Hogg, James (Henry Stewart Talks, 2013)
Progressive airflow limitation in COPD, Effect of small airway occlusion on survival, Methods of assessing lung structure, The role of the innate and adaptive immune systems in COPD, Bronchiolar destruction, Airway remodeling